A new striped Osteogaster (Siluriformes: Callichthyidae) from the Madeira and Tapajós river basins, Brazil, with a new generic diagnosis and an identification key to the species of Osteogaster - Luiz Fernando Caserta Tencatt; Vandergleison de Carvalho; Hugmar Pains da Silva; Marcelo Ribeiro de Britto (Neotropical Ichthyology, 2025)
Abstract A new species of Osteogaster is described from the Aripuanã and Juruena river basins, rio Amazonas system, differing from its congeners by having the following combination of features: (I)a conspicuous, oblique dorsolateral dark stripe on flanks, from first dorsolateral body plate to middle portion of caudal-fin base, variably extending diffuse on ventral lobe of caudal fin, and (II) posterolateral portion of scapulocoracoid moderately developed, not expanded mesially. In the light of the new data presented in a recent publication led by the first author, Osteogaster is herein diagnosed by the following combination of features: (I) mesethmoid moderate in size, (II) posterior margin of pectoral-fin spine with all or nearly all serrations directed towards the tip of the spine or perpendicularly directed, (III) posterior laminar expansion of infraorbital 2 contacting pterotic–extrascapular, (IV) anterodorsal edge of infraorbital 2 expanded anteriorly, and (V) ground color of body yellowish orange to reddish orange, with only a single, large dark patch on flanks; all fins devoid of dark spots. The distribution and exclusiveness of key morphological features present in distinct genera of Corydoradinae are discussed. Furthermore, an identification key to the species of Osteogaster is also provided.